A closer look at hybrid agile implementation in China - Yilin, Li; Maidin, Siti Sarah; Yahya, Norzariyah; Awang Abu Bakar, Normi Sham (Auricle Global Society of Education and Research, 2024)
A software project must be developed based on specific software development models or frameworks such as the Waterfall model, agile methodologies or any suitable development approaches as needed by the software development team. The need to refer to a model or framework is to ensure that the project is systematically managed, the progress is monitored, and a project meets the requirements with a good quality project that is delivered to the end-users on time. Hybrid agile is a software development lifecycle model currently widely used in a software project. Waterfall and Scrum are two examples of a well-known hybrid agile model. Some software projects even use three combinations of a model that derives a hybrid agile model called Water-Scrum-Fall. Despite many successful stories on the hybrid agile implementation and a list of benefits of the project implementing hybrid agile being reported, it is unfair to make a generic assumption that hybrid agile is acceptable by the majority of software projects. This research explores another perspective of hybrid agile implementation in one East Asian country, China. This research adopted semi-structured interviews to explore the perspective of China’s software engineering team on the hybrid agile implementation, and thematic analyses is used as the analysis approach. The finding shows that the software engineering team is inclined towards hybrid agile but acknowledges the advantages of hybrid agile.